2016
DOI: 10.1111/spc3.12265
|View full text |Cite
|
Sign up to set email alerts
|

The Intention–Behavior Gap

Abstract: Bitter personal experience and meta-analysis converge on the conclusion that people do not always do the things that they intend to do. This paper synthesizes research on intention- The Intention-Behavior GapGoal intentions are people's self-instructions to achieve desired outcomes (e.g., "I intend to finish this paper before I die!"; Triandis, 1980) and behavioral intentions are self-instructions to perform particular actions directed towards attaining these outcomes (e.g., "I intend to spend Monday morning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

37
886
5
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,366 publications
(939 citation statements)
references
References 154 publications
(189 reference statements)
37
886
5
11
Order By: Relevance
“…that colleagues would see them as show-offs; De Cocker et al, 2015). The so-called intention-behaviour gap is a phenomenon that is frequently observed in health behaviour (Sheeran, 2002;Sheeran & Webb, 2016). People often have intentions to perform a certain health behaviour but fail to do so in the face of obstacles, in this case sitting down is easier than overcoming the perceived barriers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…that colleagues would see them as show-offs; De Cocker et al, 2015). The so-called intention-behaviour gap is a phenomenon that is frequently observed in health behaviour (Sheeran, 2002;Sheeran & Webb, 2016). People often have intentions to perform a certain health behaviour but fail to do so in the face of obstacles, in this case sitting down is easier than overcoming the perceived barriers.…”
mentioning
confidence: 99%
“…Altering the environment in such a way that the intended behaviour is acted upon almost automatically is one way to overcome this intention-behaviour gap (Sheeran, 2002;Sheeran & Webb, 2016). Adapting the environment to steer people towards the healthy option, without forbidding alternative options or changing economic incentives is referred to as nudging (Thaler & Sunstein, 2008).…”
mentioning
confidence: 99%
“…Indeed, evidence of this socalled 'intention-behavior gap' (e.g. Rothman et al 2015;Sheeran and Webb 2016) has been reported across a range of consumer behaviors (e.g. Ji and Wood 2007;Young, Hwang, McDonald, and Oates 2016).…”
mentioning
confidence: 99%
“…We also explored intentions to prevent weight gain as opposed to behaviour, in line with previous work [15,38]. However, intentions do not always translate into behaviour change [41], and further studies should incorporate measures of behaviour in order to investigate how the predictors identified in this study relate to actual weight gain prevention. …”
Section: Discussionmentioning
confidence: 97%